Digitization of theses and dissertations in universities in developing countries: strategies for Makerere University - Magara, Elisam; Mayega, Stephen (My University, 2005)
Digitisation of libraries is currently described as cost effective way that has the ability to organise, store, preserve, retrieve, and ensure effective usage of information. Digitization of theses and dissertations offers great opportunities for access with immense potentials in the developing world. However, many institutions in developing countries are faced with a lot of challenges in an attempt to work towards digitisation of theses and dissertations. This paper aims at providing a roadmap for the digitisation of theses and dissertations in Makerere University. The study established the challenges and prospects of the digitisation of theses and dissertation to provide a way forward for the digitisation strategy. A qualitative approach design with a purposive sampling strategy was adopted. The results indicated that lack of skills in digital technology is a major challenge in the digitisation of theses and dissertations. It was also clear that providing a roadmap for digitisation of theses and dissertations requires a strategy for copyright protection, preservation policy, and publicity and awareness of the digitised information. The strategies for the provision of skills in digital technology, providing appropriate facilities, formulation of policies, and ensuring publicity and awareness provided a roadmap for the digitisation process in Makerere University.